Hubungan Maternal Dietary Diversity terhadap Minimum Acceptance Diet pada Anak dalam Pencegahan Stunting: Systematic Review: Hubungan Maternal Dietary Diversity terhadap Minimum Acceptance Diet pada Anak dalam Pencegahan Gizi Buruk di Negara Berkembang: Systematic Review - Atmaka, Dominikus Raditya; Wulandari, Fatqiatul; Dhorta, Nandia Firsty; Rachmah, Qonita; Setyaningtyas, Stefania Widya; Rifqi, Mahmud Aditya; Diana, Rian; Fitria, Anisa Lailatul; Pratiwi, Azizah Ajeng; Simangunsong, Tiara Tivany; Haryana, Nila Reswari; Nastiti, Aliffah Nurria; Agustin, Asri Meidyah (Universitas Airlangga, 2024)
Background: The MAD in children has an important role in preventing the risk of undernutrition. MAD in children is often associated with MDD in mothers because the mother's consumption pattern continues to feed the child who is born. Objectives: This systematic review aims to examine the relationship between MDD in mothers and MAD in children, and its role in undernutrition prevention. Methods: Articles were selected using the PRISMA method. Articles were obtained from Sciencedirect, Medline, and Embase in the 2017-2022 timeframe without data restrictions. The vocabulary used in the search is